PERKEMBANGAN PRINSIP TANGGUNG GUGAT PRODUK DI BELANDA - Sri Handajani (Perspektif, 2004)
Recently, product tanggung gugat is often spurng on surface because of the development or new technology and consumptive behaviour on the community. Therefore, it necessarily needs understanding on some principles of product tanggung gugat. These principles cover: Open Norm principle, relationship of tanggung renteng principle, risk tanggung gugat principle, and own mistakes principle.